Pengaruh Pemberian Bahan Organik Terhadap Sifat Fisik dan Sifat Kimia Tanah di Kebun Sei Putih PT. Perkebunan Nusantara IV Regional I - Aziz, Alfin; Gunawan, Hari (Dinasti Research, 2026)
This study aims to determine the effect of organic matter application on the physical and chemical properties of soil in oil palm plantations at Sei Putih Plantation of PT. Perkebunan Nusantara IV Regional I. The study was conducted from October to December 2025 using a composite sampling method at three treatment points, namely dead fences, oil palm empty bunch application areas (tankos), and plant discs, with a total of 15 samples. The parameters observed included soil physical properties (bulk density, porosity, and texture) and soil chemical properties (pH, organic C, total N, available P, and soil K). The results showed that the bulk density value ranged from 1.32–1.37 gr/cm³, with the lowest value in the organic matter application area. Soil porosity ranged from 48.17%–50.19%, showing an inverse relationship with bulk density. Soil texture was dominated by sandy loam and sandy clay loam. The chemical properties of the soil show a pH ranging from 5.26 to 5.60 (slightly acidic), organic C content of 1.23% to 2.01%, total N content of 0.58% to 0.85%, available P content of 10.65 to 12.13, and soil K content of 0.36 to 0.70. In general, the application of organic matter in the form of empty oil palm bunches has an effect on improving the physical and chemical properties of the soil, although statistical analysis does not show significant differences between treatments. However, the application of organic matter still has the potential to improve soil quality sustainably in oil palm plantations.